PENGARUH KUALITAS PELAYANAN, KREATIFIAS PROMOSI DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN (STUDI KASUS PELANGGAN GEPREK KAK ROSE PADA KADER PMII RAYON ALFARABI KOMISARIAT UNIVERSITAS ISLAM MALANG) - Ahmad Ary Setiawan; N. Rachma; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to determine the simultaneous and partial effect of service quality, promotion and brand image on Geprek customer loyalty, Sis Rose on Pmii Cadre Rayon Alfarabi, Islamic University Malang Commissariat. The method used in this research is to use quantitative methods. the population in this study amounted to 200 respondents and the sample amounted to 67 respondents using purposive sampling method. The method of analysis of this study uses multiple linear regression. The results of this study indicate that there is a relationship between service quality variables and brand image except promotion variable with , simultaneously the variable service quality promotion and brand image has a significant effect and partially only promotions that have no significant effect dont signifcant effect.Keywords: service quality promtional creafity and brand image on employed customer servies